2009
DOI: 10.1016/j.envexpbot.2009.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Defensive responses of Pinus pinaster seedlings to exogenous application of methyl jasmonate: Concentration effect and systemic response

Abstract: Methyl jasmonate (MeJa) is a plant chemical elicitor which has been used to artificially induce chemical defensive responses and resistance against herbivores in many plant species in recent decades. In this paper, we studied the effect of exogenous MeJa application at different concentrations (0, 5, 50, and 100 mM) on growth, chemical defences and resistance against the large pine weevil Hylobius abietis L in one year old Pinus pinaster Ait. seedlings. We also investigated whether the local application of MeJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 37 publications
8
103
3
Order By: Relevance
“…When seedlings were about 6 months old (25 th of April), the pots were divided into four groups, and the following treatments were applied: (i) spraying of seedlings with water and, 1 month later, inoculation with F. circinatum; (ii) spraying with an aqueous solution of MeJA (25 mM) and, 1 month later, inoculation with F. circinatum; (iii) spraying with MeJA (25 mM); and (iv) spraying water (control treatment). The MeJA dose was selected according to Moreira et al (2009). Each treatment consisted of 45 plants distributed among two blocks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…When seedlings were about 6 months old (25 th of April), the pots were divided into four groups, and the following treatments were applied: (i) spraying of seedlings with water and, 1 month later, inoculation with F. circinatum; (ii) spraying with an aqueous solution of MeJA (25 mM) and, 1 month later, inoculation with F. circinatum; (iii) spraying with MeJA (25 mM); and (iv) spraying water (control treatment). The MeJA dose was selected according to Moreira et al (2009). Each treatment consisted of 45 plants distributed among two blocks.…”
Section: Methodsmentioning
confidence: 99%
“…Evaluating methyl jasmonate for induction of resistance abietis (Heijari et al, 2005;Moreira et al, 2009 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Each plant received 4.5±0.5 ml of solution applied to the foliage with a handheld sprayer to runoff. MJ dose and concentration were determined based on previous studies where we observed that exogenous application of MJ and real herbivory increased the concentration of resin in the stem and total phenolics in the needles by equivalent magnitudes (Moreira et al, 2009(Moreira et al, , 2012c). To avoid cross-contamination, the MJ treatment was applied in a separate greenhouse chamber where plants remained for a 24-h period to allow drying of the solution.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%